05 White matter tract changes in the primary progressive aphasias. Issue 3 (15th February 2011) - Mahoney, C J; Malone, I; Buckley, A; Rosser, M N; Fox, N C; Warren, J D
Abstract : Introduction: The primary progressive aphasias (PPA) are a group of neurodegenerative language-led dementias. Three major subtypes are recognised: progressive nonfluent aphasia (PNFA) characterised by speech apraxia and agrammatism; semantic dementia (SemD), characterised by loss of vocabulary due to primary semantic memory impairment; and logopenic aphasia (LPA), characterised by word-finding pauses, anomia, and impaired phonological memory. Other subtypes have been proposed including aphasia associated with progranulin mutations (GAA). Whereas considerable progress has been made in defining profiles of cortical atrophy in PPA, information about white matter tracts connecting cortical areas remains limited. Here we addressed this issue using diffusion tensor tractography in a cohort of patients with PPA. Methods: 20 consecutive patients with a clinical diagnosis of PPA (7 SemD, 6 PNFA, 5 LPA, 2 GAA) and 12 age-matched healthy controls underwent volumetric brain MRI with diffusion tensor imaging (DTI). White matter tract changes in each group and inter-group differences were assessed using Tract Based Spatial Statistics (http://www.fmrib.ox.ac.uk/fsl/tbss ). Results: PPA syndromic groups showed well-defined fractional anisotropy, axial and radial diffusivity changes tracking white matter pathways implicated in language processing. Compared with healthy individuals, all PPA groups showed changes in the anterior superior longitudinal fasciculus (SLF), and additional tracts were involved in particular subgroups (in SemD, inferior longitudinal fasciculus (ILF), uncinate fasciculus (UF), and commissural pathways; in PNFA, more posterior SLF; in LPA and GAA, ILF). Inter-group comparisons showed significantly greater involvement of ILF and UF in SD than in PNFA or GAA; and greater involvement of left ILF in GAA than PNFA. Tract alterations were restricted to the left hemisphere in GAA but bi-hemispheric in other syndromes. Discussion: PPA syndromes are associated with distinctive profiles of altered white matter tract integrity and these tract changes provide substrates for the dysfunction of specific language networks in PPA.